to solve the following:
4-s over 7-s = 3 over s-7...
LCD is s-7
(s-7)(4-s over 7-s) = (s-7) (3 over s-7)?
am I on the right track???
ALGEBRA - Reiny, Wednesday, March 10, 2010 at 1:19pm
4-s over 7-s = 3 over s-7
(4-s)/(7-s) = 3/(s-7)
notice one denominator is the negative of the other, so
(s-4)/(s-7) = 3/(s-7)
s - 4 = 3
s = 7
BUT;, s = 7 makes our denominators zero and our fractions would be undefined, so ...
ALGEBRA - GGIFT, Wednesday, March 10, 2010 at 6:00pm
i forgot about the zero thing. thank you